Breaking the breach in Latin America: A pilot study of mechanical thrombectomy in the public healthcare system in Chile. Issue 1 (February 2021) - Rivera, Rodrigo; Amudio, Cristian; Brunetti, Enzo; Catalan, Pascual; Sordo, Juan Gabriel; Badilla, Lautaro; Echeverria, Daniel; Cruz, Juan Pablo; Ojeda, Hector; Bravo, Loreto; Bravo, Fabian; Gonzalez, Walter; et al.
Background: Mechanical Thrombectomy (MT) is the standard of care for treatment of large vessel occlusion stroke. Until the beginning of 2020 MT was not funded nor widely implemented at the public healthcare level in Chile. Objective: To describe the results of a pilot program created to provide access to public MT in Santiago - Chile. Methods: Analysis from a prospectively collected database of MT cases performed between September 2017 and September 2019 in one center. A stroke network was developed with a single MT capable stroke center and five primary stroke centers. The primary efficacy endpoint was the rate of functional independence (mRS 0-2) at 90 days. Successful reperfusion was defined as 2 b-3 according to the thrombolysis in cerebral infarction scale. Safety outcomes include the rates of symptomatic intracranial hemorrhage and 90-day mortality. Results: A total of 100 patients were treated over the study period. Their mean age was 62.8 ± 11.8 years and median baseline National Institute of Health Stroke Scale (NIHSS) measurement was 17. Seventy-seven percent of the patients received intra venous thrombolysis. Successful reperfusion was achieved in 95% of the cases. NIHSS at 24 hours showed a median drop of 7 points from baseline (p < 0.00001) and 50% of the follow-up patients were functionally independent at 90 days. Symptomatic Intracerebral hemorrhage occurred in 5% of the patients and 90-day all case mortality was 11%. Conclusions: We demonstrated the feasibility of a publicly funded MT program in Chile, with similar results as other international randomized control trials.